Bicentennial memory: Bogota’s Eastern Mountains (1810-2010). A review of the current state of knowledge (2013)
Review article that compiles mostly published literature about Bogota’s Eastern Mountains over the last two centuries, between 1810 and 2010, including 255 written works among research consultancy reports, government projects, regulatory bodies’ follow-ups and evaluations, undergraduate and graduate thesis, letters, news bulletins, scientific papers of national and international journals, books, official policies, and audiovisual presentations. All found documents were sorted within four fields of knowledge: social sciences, natural sciences, technical/environmental sciences, and local facts; three main characteristics were analyzed: i) Scope: basic, practical, theoretical. ii) Approach: disciplinary, interdisciplinary, transdisciplinary. iii) Team: one researcher, two researchers, research group; and the following frameworks were considered: administrative, historical, ecological, cultural, and human-rights advocacy.